Pemanfaatan Ekstrak Spirulina Platens Sebagai Bio-Material Kamuflase Multifungsi Untuk Samaran TNI Yang Melindungi Kulit Dari Radiasi, Panas, Dan Kondisi Lingkungan Ekstrem - Azza, Athira; Aritonang, Sovian (Fakultas Teknik UMSU, 2025)
Spirulina platensis is a species of microalgae from the cyanobacteria group known for its high nutritional value and extensive health benefits. This microalgae is spiral or helical in shape and bluish green in color due to its phycocyanin content, a protein pigment that also has antioxidant properties. Spirulina platensis is often used as a food supplement because of its high protein content, reaching 50-70%, and contains vitamins, minerals, and essential fatty acids that support health. This study developed a peel-off gel mask from Spirulina platensis extract with Polyvinyl Alcohol (PVA) and Hydroxypropyl Methylcellulose (DMC) as gelling agents in various compositions. Formulas with a ratio of PVA 2.25%: DMC 1.25% (formula A) and PVA 2.00%: DMC 1.05% (formula B) showed good physical stability, including pH close to skin pH, viscosity, and ideal drying time. These results show the potential of Spirulina platensis as a multifunctional camouflage material that can protect the skin from UV radiation and extreme environmental conditions.